Using the Commutative Property, we can rearrange the terms in any order without changing their sum.
For the first expression, we can rearrange the terms as follows:
5 + 1 + 7 = 1 + 5 + 7
For the second expression, we can rearrange the terms as follows:
4 + 7 + 1 = 1 + 4 + 7
Therefore, the two algebraic expressions are equivalent when we fill in the blanks:
5 + ____ + 1 + 7 = 4 + ____ + 7 + 1
Using the Commutative Property, fill in the blanks so that the two algebraic expressions are equivalent.
5+ +1+7=4+ +7+1
1 answer